Standarisasi Pelayanan Kedokteran Sebagai Upaya Preventif Malpraktek Kedokteran Dalam Perspektif Hukum - Alfis Setyawan (Journal of Judicial Review, 2016)
Act No. 36 year 2009 on Health and Act No. 29 year 2004 on Doctoral Practice were not enough to regulate about the doctoral service standardization. The doctoral service standardization as a national minimum standard was very required. The doctoral service standardization had to be in the legal regulation form so that it’s binding, had a law force, and at the same time became a doctoral malpractice preventive action because doctors had the legal obligations to do the practice based on the doctoral service standardization.